Photophysical Details and O2-Sensing Analysis of a Eu(III) Complex in Polymer Composite Nanofibers Prepared by Electrospinning - Cui, Chunguo; Song, Lina; Li, Chao; Lin, Tiantian; Shi, Kaiyao (Frontiers in Chemistry, 2022)
A novel Eu(III) complex of Eu(N-DIIQ)(TTA)3 (N-DPIQ = N-ethyl-dipyrido [f,h] indolo [3,2-b] quinoxaline, TTA = 2-thenoyltrifluoroacetonate) is synthesized and characterized, and the energy transfer mechanism between ligands and Eu(III) center is studied. It is observed that the emission intensity of Eu(III) complex greatly dependents on oxygen concentration, and oxygen-sensing properties of the Eu(III) complex in polymer composite nanofibers of poly(vinylpyrrolidone) (PVP) prepared by electrospinning are investigated. Results reveal that the decrease of emission intensity for Eu(III) complex is caused by the ground state (triplet) oxygen quenching on antenna ligands triplet state, and the Eu(N-DPIQ)(TTA)3/PVP composite nanofiber with a loading level of 6 wt% exhibits the best result with a sensitivity of 2.43, a short response time of 10 s, and good linearity..